Label-free protein assay with site-directly immobilized antibody using self-actuating PZT cantilever - Kang, Ghi Yuun; Han, Ga Young; Kang, Ji Yoon; Cho, Il-Hoon; Park, Hyung-Ho; Paek, Se-Hwan; Kim, Tae Song (ELSEVIER SCIENCE SA, 2006)
This paper reports a method to improve the limit of the label-free detection of myoglobin using site-directed immobilization on the surface of self-actuating PZT cantilever sensor. The resonant frequency change of cantilever was measured electrically using piezoelectricity when antibody-antigen interaction occurred. Site-directed antibody was biotinylated after reducing the binding region to hinge region of randomly biotinylated antibody, which increased the number of effective binding sites. Investigating the effect of site-directed antibody on the cantilever sensor revealed that this protocol was able to enhance the performance of analytical sensitivity about 10 times with the modification of sensing layer. The experimental results demonstrated this biosensor can be used for diagnosis of acute myocardial infarction in clinical range of tens of ng/ml. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ELECTRICAL DETECTION; CARDIAC MARKERS; MICROCANTILEVER; POINT